Unintended Avulsion of Hypertrophic Adenoids in Posterior Nasopharynx: A Case Report of a Rare Complication Caused by Nasotracheal Intubation. (25th June 2014) - Chen, Hao-Hu; Chen, Li-Chuan; Hsieh, Yu-Hui; Chen, Mao-Kai; Chen, Chung-Ho; Cheng, Kuang-I
Abstract : The enlarged adenoid serves as a mechanical obstacle on the nasopharynx to intricate nasotracheal intubation. No matter what video or direct laryngoscopic techniques are applied, nasotracheal tube navigation from the nasal valve area through the nasal cavity to the nasopharynx is always blind; trauma is not uncommon. Here we report a case of unintended avulsed adenoids that plugged the tube tip while the nasotracheal tube blindly navigated through the nasopharyngeal space. After failing to insert a bent tip of gum elastic bougie passing through the nasopharynx, an alternative method of NTI was performed by mounting the nasotracheal tube on a fiberoptic bronchoscope. The nasotracheal tube was successfully railroaded along the insertion tube of the fiberscope to the trachea.